Prekmursko vprašanje do podpisa Trianonske pogodbe - Bajc, Gorazd (Studia Historica Slovenica, 2020)
In the article, the authors displayed the view of Great Britain considering the demarcation in Prekmurje at the end of First World War. In order to better understand the titular theme, they firstly presented the basic characteristics of this northeastern most part of Slovenian ethnic territory. Secondly, they focused their attention on the British understanding of interethnic conflicts in Hungary on the eve of the events of the war as well as their comprehension of the dangers of Bolshevism during the last phase of the war and afterwards. At the core of the article, they focused on the question of demarcation at the Paris Peace Conference, when it was determined Prekmurje should be included into the Kingdom of Serbs, Croats and Slovenes.
Keywords: boljševizem; Bolshevism; Great Britain; Hungary; Kingdom of Serbs, Croats and Slovenes; Kraljevina SHS; Paris Peace Conference; pariška mirovna konferenca; politična zgodovina; Prekmurje; Velika Britanija